Effects of insider trading on market efficiency and volatility in Bursa Malaysia - Lye, Wing Fah (2011)
The general objective of this study is to investigate evidence for strong-form informational efficiency of Bursa Malaysia. It provides evidence for whether outside investors can use information about insider transactions to earn abnormal profits. Additionally, the study attempts to establish evidence for market volatility as a result of insider trades. These three objectives are examined in reference to the efficient market hypothesis, rational expectation theory, utility theory, random walk theory, noise theory and chaos theory. This study is important because of the investment implications of insider trading as they are of special interest to stock investors, analysts, policy-makers, regulators and to a certain extent, the academic community. Each group looks at insider trading from a different perspective and how investors and the market in general can benefit from insider activities. The contribution of the study is clarifying whether insider trading is beneficial or destructive to Bursa Malaysia. The research uses insider trading data of Bursa Malaysia sourced from Bloomberg, Singapore and I-capital Malaysia. The insider transactions involve filings made to Bursa Malaysia from 1 July 2003 to 30 June 2008. The number of insider transactions is 5799 which were transacted from 70 KLCI component stocks. This study uses the market model to investigate the availability of abnormal profits to insiders and the GARCH model to study the effect of insider trading on the volatility of Bursa Malaysia. In order to examine whether insider trading exists in Bursa Malaysia and whether it is strong form inefficient, the average cumulative abnormal returns (ACAR) are plotted separately for insider buy and insider sell transactions. Generally, average cumulative abnormal returns from insider buy transactions tend to be positively sloped. After buying, share prices will still go up. Insider sell transactions also maximize returns prior to insiders disposing off their shares. After selling, the share prices will come down. Numerous studies conclude that insiders earn significant abnormal profits by trading the securities of their own firms. Estimates of insiders’ profits of these studies range from 3% to 30% during holding periods of eight months to three years. The result for insider buys is found to be within expectation. It enables insider buy to make approximately 3.2% abnormal profits from owning a security from event day up to 114 days. However, the result turns out to be completely different for insider sells which is inconsistent with existing theory. After selling, there are still abnormal profits of 7.01% over 91 days. This suggests that there is collusion with a third party to make abnormal profits for insider sell. It is argued that the evidence is indicative of manipulation of the stock prices by insider collusion. The results of CAR also provide evidence that insider trading exists in Bursa Malaysia. The existence of insider profits has been considered as evidence inconsistent with the strong form of efficient market model. As the market is not able to price to fully reflect insider information of buy transactions, this means that there is still room for abnormal profit to be made even after the information is made public which is consistent with the Chaos Theory. Hence, Bursa Malaysia market is strong form inefficient. There is also academic evidence showing that outsiders who mimic the trading activities of insiders cannot make abnormal profits. This evidence is inconsistent with anecdotal evidence frequently mentioned in the press which shows that those outsiders who mimic the trades of insiders can earn abnormal profits. Numerous studies also give the same conclusion. However, there are studies with evidence that outsiders who mimic insiders are unable to make abnormal profits. This is consistent with semi-strong form efficiency. From the study, outsiders can mimic the action of insiders to earn average abnormal profit of 2.86% for a period of 100 days. As this is a serious exception to the efficient market hypothesis, these outsiders violate semi-strong form market efficiency. The study also shows that insider trading does influence and affect the market volatility of 38% of insider trades. Knowing that insider trading is a criminal offence, 62% of insiders will ensure that their trading does not affect the volatility of the market. Insiders may disguise their trading with stock pooling and friendly syndicates. A pattern has emerged in Bursa Malaysia that stock prices drop more violently, stock prices drop more than go up and there is also a tendency for stock prices to drop more often. With this discovered knowledge, insiders will go for piggy-backing on insider trades and trading intensity. The study concludes that the unfairness and volatility of insider trading will cause loss of investor confidence. Insider trading is not beneficial and can have adverse effects on Bursa Malaysia.